PENGARUH SENAM ERGONOMIK TERHADAP KUALITAS TIDUR PADA LANSIA DENGAN GANGGUAN TIDUR DI UPTD GRIYA WERDHA JAMBANGAN SURABAYA - DYAH WIJAYANTI; Tumini Tumini; Dewi Anita Sari (Akademi Keperawatan Dharma Husada Kediri, 2019)
The higher the life expectancy of a country causes the high number of elderly to be followed by the high health problems that exist in the elderly, including a decrease in the quality of sleep. Ergonomic exercise can increase serotonin which can make feel calm, sleepy and improve sleep quality. This study aims to analyze the effect of ergonomic exercise on the quality of elderly sleep in Griya Werdha Surabaya. The study design used a pre-experimental one group pretest-posttest design. The sampling technique in this study uses probability sampling by means of simple random sampling. The independent variable of this study is ergonomic exercise and the dependent variable is the quality of sleep. Data collection used a sleep quality questionnaire before and after ergonomic exercise. Data analysis using the Wilcoxon signed rank test. The results of this study found a significant difference between the quality of sleep before and after being given ergonomic exercise, it founded at 36 elderly (69.2%) experienced an increase in sleep quality. Wilcoxon analysis showed that ergonomic exercise had an effect on improving sleep quality in the elderly at Griya Werdha Jambangan Surabaya (p = 0,000). Based on the results of this study ergonomic exercise can be used as one of the therapies to improve sleep quality in the elderly. Keywords: elderly, ergonomic exercise, sleep quality